La Bibliothèque pastorale de Paul Chaussard (1803) - Christian Leroy (Etudes Epistémè)
Taking the critical anthology of pastoral poetry from its Biblical origins to the end of the XVIIth century as its starting point, the Bibliothèque pastorale, written by Paul Chaussard in 1803, poses the problem of the persistence of the dramatic pastoral genre in the XVIIIth century. Although it is most of the time unknown, this persistence is confirmed by the selecting criterion, which is essentially dramatic, by the promotion of a modern dramatic pastoral written in prose and by the promotion of the mixed genre of the moralizing narrative pastoral, in which love is replaced by duty.